A phase 2 dose‐finding study of lonafarnib and ritonavir with or without interferon alpha for chronic delta hepatitis. Issue 6 (23rd December 2021) - Yurdaydin, Cihan; Keskin, Onur; Yurdcu, Esra; Çalişkan, Aysun; Önem, Soner; Karakaya, Fatih; Kalkan, Çağdaş; Karatayli, Ersin; Karatayli, Senem; Choong, Ingrid; Apelian, David; Koh, Christopher; et al.
Abstract: Background and Aims: Proof‐of‐concept studies demonstrated lonafarnib (LNF), a first‐in‐class oral prenylation inhibitor, efficacy in patients infected with HDV. The lonafarnib with ritonavir for HDV‐2 (LOWR‐2) study's aim was to identify optimal combination regimens of LNF + ritonavir (RTV) ± pegylated interferon alpha (PEG‐IFNα) with efficacy and tolerability for longer‐term dosing. Here we report the safety and efficacy at end of treatment for up to 24 weeks. Approach and Results: Fifty‐five patients with chronic HDV were consecutively enrolled in an open‐label, single‐center, phase 2 dose‐finding study. There were three main treatment groups: high‐dose LNF (LNF ≥ 75 mg by mouth [po] twice daily [bid] + RTV) ( n = 19, 12 weeks); all‐oral low‐dose LNF (LNF 25 or 50 mg po bid + RTV) ( n = 24, 24 weeks), and combination low‐dose LNF with PEG‐IFNα (LNF 25 or 50 mg po bid + RTV + PEG‐IFNα) ( n = 12, 24 weeks). The primary endpoint, ≥2 log10 decline or < lower limit of quantification of HDV‐RNA from baseline at end of treatment, was reached in 46% (6 of 13) and 89% (8 of 9) of patients receiving the all‐oral regimen of LNF 50 mg bid + RTV, and combination regimens of LNF (25 or 50 mg bid) + RTV + PEG‐IFNα, respectively. In addition, multiple patients experienced well‐tolerated transient posttreatment alanine aminotransferase increases, resulting in HDV‐RNA negativity and alanine aminotransferase normalization. The proportions of grade 2 and 3 gastrointestinal adverse events in the high‐dose versus low‐dose groups were 49% (37 of 76) and only 22% (18 of 81), respectively. Conclusions: LNF, boosted with low‐dose RTV, is a promising all‐oral therapy, and maximal efficacy is achieved with PEG‐IFNα addition. The identified optimal regimens support a phase 3 study of LNF for the treatment of HDV.